Forever 'Becoming'? Negotiating Gendered and Ageing Embodiment in Everyday Life. (December 2020) - Pilcher, Katy; Martin, Wendy
Drawing upon 62 participant-produced visual diaries and accompanying interview narratives, this article explores the significance of everyday body work for people in mid- to later life. Departing from previous work that has explored the intersections of gender and age in relation to a single embodied practice, this article highlights the salience of a myriad of bodily practices for the everyday ways that gender and ageing identities are constituted, specifically hair styling, beauty work, clothing, and dieting. We argue that women negotiate a gendered pressure to age well, which results in an in/visibility paradox, in which they are at one and the same time seen, but not seen. Consequently, we question whether women are thus forever 'becoming' – attempting to become embodied subjects, alongside subjecting to 'becoming' – aligning with normative discourses. The article examines the competing ways that ageing and gendered bodies are constructed, together with participants' embodied resistance to negative normalising discourses.